2007
DOI: 10.1289/ehp.9863
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Traffic-Related Air Pollution and Exposure to Violence on Urban Asthma Etiology

Abstract: BackgroundDisproportionate life stress and consequent physiologic alteration (i.e., immune dysregulation) has been proposed as a major pathway linking socioeconomic position, environmental exposures, and health disparities. Asthma, for example, disproportionately affects lower-income urban communities, where air pollution and social stressors may be elevated.ObjectivesWe aimed to examine the role of exposure to violence (ETV), as a chronic stressor, in altering susceptibility to traffic-related air pollution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
228
2
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(246 citation statements)
references
References 56 publications
10
228
2
6
Order By: Relevance
“…These findings suggest that early-life exposures to traffic pollutants may affect asthma severity and development. This view is supported by studies [12][13][14][15][16][17][18] of preschool children that have found increased risk of incident asthma or wheeze or cough without a cold from long-term exposures to local trafficrelated air pollutants using GIS-based methods. A recent study 35 showed acute increases in wheeze occurrence with elevations in daily regional NO 2 and NO x levels in infants and children followed up during their first 3 years of life.…”
Section: Overview Of Findings and Implicationsmentioning
confidence: 88%
See 1 more Smart Citation
“…These findings suggest that early-life exposures to traffic pollutants may affect asthma severity and development. This view is supported by studies [12][13][14][15][16][17][18] of preschool children that have found increased risk of incident asthma or wheeze or cough without a cold from long-term exposures to local trafficrelated air pollutants using GIS-based methods. A recent study 35 showed acute increases in wheeze occurrence with elevations in daily regional NO 2 and NO x levels in infants and children followed up during their first 3 years of life.…”
Section: Overview Of Findings and Implicationsmentioning
confidence: 88%
“…9 High home or school traffic density has been associated with prevalence of diagnosed asthma in epidemiologic studies. 10,11 Cohort studies [12][13][14][15][16][17][18] have shown associations between asthma incidence or early wheeze or cough without a cold and traffic-related air pollution near the homes of preschool children using geographic information system (GIS)-based exposure models.…”
Section: Introductionmentioning
confidence: 99%
“…10,64,67,68 Risk factors may interact to affect health, as shown by research on the synergistic effects of air pollution and exposure to violence in relation to asthma among urban children. 69 Future research must address psychological factors over the lifecourse, the relative importance of chronic and acute stressors, 70 the possibility that the asthma phenotype is programmed before birth, 17 and reverse causality, since stress and consequent problems may be caused or aggravated by having asthma or caring for someone with asthma. [70][71][72][73] In addition to an ecological perspective, longitudinal data and a multi-level approach are required to understand structural forces that influence the distribution of housing stressors-and as a result, psychological stress.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important environmental factors that has been problematic in recent decades especially among urban societies and could raise the serum level of inflammatory cytokines by affecting gut microbiota function is air pollution [18,[22][23][24][25]. Oral route accounts for much of the exposure to air pollutants and human studies have shown that larger particles are quickly cleared from the lungs and transported to the intestinal tract by mucociliary clearance [26].…”
Section: Discussionmentioning
confidence: 99%